Evolution and modulation of a poleward‐propagating anticyclonic eddy along the Japan and Kuril‐Kamchatka trenches. Issue 6 (18th June 2015) - Kaneko, Hitoshi; Itoh, Sachihiko; Kouketsu, Shinya; Okunishi, Takeshi; Hosoda, Shigeki; Suga, Toshio
Abstract To investigate the relationships between the movement of an eddy and its interior structure and water properties, four profiling floats were deployed in an anticyclonic eddy in the western North Pacific in 2013 (April–October). Daily float profiles showed rapid changes in temperature and salinity corresponding to strong interactions between eddies north of the subtropical Kuroshio Extension. After the first interaction with a warm‐core eddy in April, the isolation of the winter mixed layer from the surface was observed, forming a subsurface remnant layer. Another interaction with a cold fresh eddy at middepths in May resulted in the formation of a multilayer structure. The eddy then moved poleward along the Japan and Kuril‐Kamchatka trenches, indicating changes in its propagation pattern coupled to its interior structure. The eddy then moved northward (June–July), stalled (July–August), and moved eastward (August–October). In addition to a general declining trend, the properties of the warm saline core changed over a short time period, coinciding with changes in propagation. A density anomaly at middepths of the eddy changed location during the stalled period; however, denser waters were continuously observed in the southeast part of the eddy during its northward and eastward movement. This unidirectional density anomaly pattern was consistent with the structure of the poleward‐propagating eddy, which interacted with the western topographic boundary. Meridional exchanges of heat and material were potentially elevated by the eddy's advection and movement, as well as by water modifications in the eddy associated with exchanges along its perimeter.